Cytogenetic Analysis of the Artificial Tetraploid Lycopersicon Esculentum var Cerasiforme - Alfonsi, C.; Cequea, H. (Ciencia, 1970)
The artificial tetraploids obtained from Lycopersicon esculentum var cerasiforme (2n= 4x = 48), were taller than diploids (2n = 2x = 24), and had larger flowers, leaves, and more hairs. All pollen grains were empty. At diakinesis was observed a low quadrivalent and a high bivalent frequency, which indicates normal pairing at pachytene, but beyond metaphase I some genes or environmental factors must disrupt the meiotic spindle in some way, producing genetically unbalance gametes with 5, 6 and 7 microspores. The low quadrivalent and the high bivalent frequency may be due to the presence of pairing control different genes in the original parent AoA1, which by doubling the genomes produce more bivalents than expected